Analisis Sektor Basis dan Non- Basis Terhadap Potensi Pertumbuhan Ekonomi - Sherly Ferdinandus; Ventje Jeffry Kuhuparuw (Univiversitas Dr. Djar Wattiheluw, 2024)
This research was conducted to identify the evolving sektors as basic and non- basic sektors in the Maluku Province during the period from 2012 to 2021, and to determine their impact on the economic growth in the Maluku Province. The findings of this study indicate that the sektors evolving as basic sektors in the Maluku Province include agriculture, forestry, and fisheries; water supply, waste management, and recycling; wholesale and retail trade, repair of motor vehicles and motorcycles; transportation and warehousing; public administration, defense, and social security; education services; health and social activities; as well as other services. Meanwhile, the sektors evolving as non-basic sektors in the Maluku Province are mining and quarrying; manufacturing industry; electricity and gas supply; construction; accommodation and food services; information and communication; financial and insurance services; real estate; and corporate services. Furthermore, both partial and simultaneous statistical tests indicate that the influence of basic and non-basic sektor variables on economic growth during the period 2012-2021 has a positive and significant impact in the Maluku Province.